2015
DOI: 10.4238/2015.april.27.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autologous SCF- and G-CSF-mobilized bone marrow stem cells on hypoxia-inducible factor-1 in rats with ischemia-reperfusion renal injury

Abstract: ABSTRACT. To explore the mechanism whereby stem cell factor (SCF) and granulocyte colony-stimulating factor (G-CSF) jointly mobilize bone marrow stem cells (BMSCs) and promote kidney repair, male Sprague-Dawley rats were randomly assigned into 4 groups. In the treatment control group, rats were administered SCF (200 μg· kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Analysis of the expression of other HIF target genes could help explain how the effects of HUCB‐MNCs on detrusor smooth muscle are mediated through the HIF pathway. Thus, we suggest that upregulation of HIF‐1α in the diabetic bladder contributes to an increase in VEGF protein, as similarly shown in a previous study …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of the expression of other HIF target genes could help explain how the effects of HUCB‐MNCs on detrusor smooth muscle are mediated through the HIF pathway. Thus, we suggest that upregulation of HIF‐1α in the diabetic bladder contributes to an increase in VEGF protein, as similarly shown in a previous study …”
Section: Discussionsupporting
confidence: 89%
“…Thus, we suggest that upregulation of HIF-1α in the diabetic bladder contributes to an increase in VEGF protein, as similarly shown in a previous study. 70 In the present study, intracavernous injection of HUCB-MNCs enhanced the smooth muscle content and levels of α-SMA (a specific marker of SMCs) in the bladder of diabetic rats. Similarly, Dong et al 47 previously reported that treatment with 2 × 10 6 urine-derived stem cells effectively improved impaired detrusor contractility by ameliorating bladder fibrosis and decreasing α-SMA protein levels and SMC apoptosis in the diabetic bladder.…”
Section: Hucb-mncs May Exert Beneficial Effects On Contractions Inducsupporting
confidence: 52%
“…Jamadarkhana et al found that administrating PHD inhibitor TRC160334 at 2 h, 6 h, and 10 h post the onset of kidney ischemia activated the expression of HIF-1 and attenuated kidney injury by inducing heat shock protein 70 (HSP70) [102]. Also, administrating granulocyte colony-stimulating factor (G-CSF) and stem cell factor (SCF) 6 h after IRI also activated the expression of HIF-1 and reduced the degree of kidney tissue injury by upregulating the expression of VEGF and EPO [103]. But, other studies demonstrated that administrating PHD inhibitors after renal ischemia had no effects in attenuating AKI and renal fibrosis [99,100].…”
Section: Hif In Aki and Mechanisms Of Hif Signaling In Akimentioning
confidence: 99%
“…Because G-CSF can mobilize progenitors from bone marrow, which home to sites of injury to mount anti-inflammatory and repair responses 32 , we wanted to test whether H/R mobilizes progenitors that home to lung tissue. Therefore, we investigated pulmonary and circulating CD133 + progenitors, which are pluripotential cells that can be mobilized by G-CSF 33 .…”
Section: Resultsmentioning
confidence: 99%